Phase-change ruthenium phosphide nano-particles as well as air laser scribing preparation method and application of phase-change ruthenium phosphide nano-particles
Through the preparation method of air laser etching, the problems of low purity, high cost and low efficiency of phase change ruthenium phosphate nanoparticles synthesis in the prior art are solved, and efficient and low-cost nanoparticles preparation is achieved, ensuring the purity of the phase.
Patent Information
- Application Number
- CN202510109755.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-03-28
AI Technical Summary
The existing synthesis methods of phase change ruthenium phosphide nanoparticles cannot ensure the purity of the phase, and are costly and have low synthesis efficiency.
Using the preparation method of air laser etching, the graphene substrate was laser etched and mixed aqueous solution of ruthenium trichloride and sodium hypophosphite was added dropwise, vacuum drying and secondary etching were performed to prepare transition group metal ruthenium phosphide nanoparticles with different phase compositions.
High-throughput preparation of ruthenium phosphide nanoparticles of different phase compositions is achieved, which improves synthesis efficiency, reduces costs, and ensures phase purity.
Smart Images

Figure CN119706760A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanomaterials, and in particular relates to a phase-change ruthenium phosphide nanoparticle and an air laser scratching preparation method and application thereof. Background Art
[0002] Ruthenium phosphide nanoparticles have shown broad application prospects in the fields of catalysis, energy storage and sensors due to their excellent catalytic and electrochemical properties. According to their different structures and properties, ruthenium phosphide can be divided into Ru2P, RuP and RuP2. Among them, in the field of catalysis, RuP2 is widely used in electrocatalytic reactions and Li-CO2 batteries, especially hydrogen evolution reaction (HER) and oxygen reduction reaction (OER). As an electrocatalyst, RuP2 has good electronic conductivity and high active sites, which can effectively reduce the overpotential of the reaction and further promote the generation of hydrogen. In terms of energy storage, RuP can effectively improve the energy density of the battery due to its high specific capacity and good cycle stability. When reacting with lithium or sodium ions, RuP can form a reversible solid solution or alloy, which not only improves the efficiency of the battery, but also enables the battery to maintain good performance during multiple charge and discharge processes.
[0003] Common methods for synthesizing phase-change ruthenium phosphide nanoparticles include ball milling, solid phase synthesis, low temperature liquid phase synthesis, and hydrothermal synthesis. These methods usually achieve the synthesis from Ru2P to RuP and then to RuP2 by continuously increasing the content of the P source, and also require a certain carrier gas (Ar gas). This not only fails to ensure the purity of the phase, but also leads to problems such as high cost and low synthesis efficiency.
[0004] Therefore, there is an urgent need for an efficient preparation method for ultrafast synthesis of phase change ruthenium phosphide. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a phase-change ruthenium phosphide nanoparticle and its air laser scratching preparation method and application, so as to solve the technical problems that the existing synthesis method of phase-change ruthenium phosphide nanoparticles cannot ensure the purity of the phase, has high cost and low synthesis efficiency.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: On the one hand, the present invention provides a method for preparing phase-change ruthenium phosphide nanoparticles by air laser scribing, comprising the following steps: A polyimide film is scratched with a laser to obtain a graphene substrate, and then a mixed aqueous solution of a ruthenium trichloride precursor salt and sodium hypophosphite is added dropwise to the graphene substrate. After vacuum drying, the graphene substrate is scratched again with a laser to obtain transition metal ruthenium phosphide of different phase compositions.
[0007] In one embodiment, when the polyimide film is scribed using a laser, the wavelength of the laser used is 10.6 μm.
[0008] In one embodiment, the laser scribing rate of the polyimide film is 7×10 3 mm / s-7×10 5 mm / s, laser power is 3W-9W, and the scratching area is (2-10)mm×(2-10)mm.
[0009] In one embodiment, the molar ratio of the ruthenium trichloride aqueous solution to the sodium hypophosphite solution in the mixed aqueous solution of the ruthenium trichloride precursor salt and the sodium hypophosphite is 1:(1-40).
[0010] In one embodiment, the concentration of the ruthenium trichloride aqueous solution is 0.05M.
[0011] In one embodiment, the concentration of the sodium hypophosphite solution is 0.05M-2M.
[0012] In one embodiment, the amount of the mixed aqueous solution of the ruthenium trichloride precursor salt and sodium hypophosphite added is (80-10000) μL.
[0013] In one embodiment, the laser scribing rate of the secondary scribing is controlled to be 7×10 3 mm / s-7×10 5 mm / s, the laser power is 1W-20W, and the scratching area is the same as the graphene substrate area.
[0014] On the other hand, the present invention also provides a phase-change ruthenium phosphide nanoparticle prepared according to the air laser scratching preparation method of the phase-change ruthenium phosphide nanoparticle, wherein the phase-change ruthenium phosphide nanoparticle is Ru2P, RuP and RuP2.
[0015] In another aspect, the present invention further provides the use of the above-mentioned phase-change ruthenium phosphide nanoparticles Ru2P, RuP and RuP2 as positive electrode materials in button-type Li-O2 batteries.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing phase-change ruthenium phosphide nanoparticles by air laser scribing. The preparation method can prepare ruthenium phosphide nanoparticles with different phase compositions in high throughput by instantaneously scribing a mixed solution of sodium hypophosphite and ruthenium trichloride hydrate supported on graphene with a pulsed laser. Ruthenium phosphide nanoparticles with a mixed phase structure can be obtained by dripping a mixed aqueous solution of a ruthenium trichloride precursor salt and sodium hypophosphite, thereby laying the foundation for the synthesis of single-phase ruthenium phosphide nanoparticles. When performing secondary scribing, the energy of the laser can meet the decomposition temperature of the mixed salt, and different scanning rates determine the cooling rate, which is crucial for the precise regulation of pure phase ruthenium phosphide. By adjusting the parameters of the laser engraving machine (such as laser power, scanning speed, etc.), the synthesis of single-phase ruthenium phosphides with three different phase structures can be finally achieved. Since the laser-induced chemical reaction is usually completed in a very short time, the synthesis efficiency of ruthenium phosphide can be significantly improved. The laser scribing method has high temperature (1500K), extremely fast heating / cooling rate (7×10 5 mm / s) and the advantages of not requiring a special protective atmosphere make it an ideal method for ultrafast synthesis of phase-change ruthenium phosphide nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The middle figures (A), (B) and (C) are respectively the refined XRD spectra of Ru2P, RuP and RuP2 of the present invention; Figure 2 The simulated Raman results and experimental Raman spectra of Ru2P, RuP and RuP2 nanoparticles of the present invention; Figure 3 The middle figures (A), (B) and (C) are TEM morphologies and high-resolution transmission electron microscopy images of Ru2P, RuP and RuP2 nanoparticles of the present invention, respectively; Figure 4 This is a first cycle overpotential performance diagram when Ru2P of the present invention is used as a positive electrode material for a lithium oxygen battery; Figure 5 The middle figures (A) and (B) are respectively the cycle performance diagrams of the Ru2P of the present invention as the positive electrode material of the lithium oxygen battery at low current density and high current density; Figure 6 The XRD patterns of the compounds prepared under different laser parameters in Example 11 of the present invention; Figure 7 The XRD patterns of the compounds prepared under different laser parameters in Example 12 of the present invention; Figure 8 1 is the XRD spectrum of the compound prepared under different laser parameters in Example 13 of the present invention. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0019] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0020] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0021] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0022] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0023] On the one hand, the present invention provides a method for preparing phase-change ruthenium phosphide nanoparticles by air laser scribing, comprising the following steps: First, a polyimide film is scratched with a laser to obtain a graphene substrate, and then a mixed aqueous solution of ruthenium trichloride (RuCl3) precursor salt and sodium hypophosphite is added to the graphene substrate. After vacuum drying, the graphene substrate is scratched again with a laser to obtain transition metal ruthenium phosphide with different phase compositions.
[0024] Another aspect of the present invention provides a phase-change ruthenium phosphide nanoparticle prepared by the above-mentioned preparation method, wherein the phase-change ruthenium phosphide nanoparticle is Ru2P, RuP and RuP2.
[0025] In another aspect, the present invention uses the prepared ruthenium phosphide nanoparticles as the positive electrode material of Li-O2 batteries and applies them to button-type Li-O2 batteries. A further inventive point is that Ru2P is used as the positive electrode material of lithium-oxygen batteries for the first time.
[0026] The specific steps of the air laser scribing preparation method of the phase change ruthenium phosphide nanoparticles are as follows: 1) First, a laser engraver with a laser wavelength of 10.6 μm was used to scratch the polyimide film to obtain a porous graphene substrate. The laser scratching rate was 7×10 3 mm / s-7×10 5 mm / s, laser power is 3W-9W, and the scratching area is (2-10)mm×(2-10)mm.
[0027] 2) Prepare a RuCl3 aqueous solution with a concentration of 0.05M and a sodium hypophosphite (NaH2PO2) aqueous solution with a concentration of 0.05M-2M, mix the RuCl3 aqueous solution and the sodium hypophosphite (NaH2PO2) solution in a certain molar ratio (1:1-1:40) and perform ultrasonic mixing for 5-10 minutes.
[0028] 3) The mixed solution was added dropwise onto the graphene substrate in an amount of (80-10000) μL, and vacuum dried for 12 h to remove the water in the mixed solution. The graphene substrate was then scribed with a laser again to obtain graphene-supported ruthenium phosphide nanoparticles with different phase structures. The laser scribe rate was controlled to be 7×10 3 mm / s-7×10 5 mm / s, the laser power is 1W-20W, the scratching area is equivalent to the area of the graphene substrate, and the laser scratching process is carried out in the air without the need for a protective atmosphere.
[0029] Furthermore, the application process of Ru2P as the positive electrode material of lithium oxygen battery is as follows: First, graphene-supported Ru2P nanoparticles and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 9:1, ground and dispersed in NMP solvent to obtain a slurry. 30 μL of the slurry was dropped onto carbon paper and dried in a vacuum drying oven for 24 hours to obtain a positive electrode for a Li-O2 battery.
[0030] Secondly, button-type Li-O2 batteries were assembled in a glove box filled with argon, and the assembled batteries were placed in a sealed test device and irrigated with O for 6 hours. 2, Then let it sit for 12 hours and connect the Land battery tester to complete the test.
[0031] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0032] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0033] Embodiment 1: The solution composition and concentration are as follows: 0.05M RuCl3 solution and 0.05M NaH2PO2 solution A method for preparing single-phase Ru2P nanoparticles: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of 4×4 cm. 2 Then, 900 μL of 0.05 M RuCl3 solution and 0.05 M NaH2PO2 mixed solution were added to the graphene substrate and vacuum dried for 12 h. The laser power was 3 W and the laser scribing rate was 3.7 × 10 5 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-supported Ru2P nanoparticles.
[0034] Embodiment 2: The solution composition and concentration are as follows: 0.05M RuCl3 solution and 0.05M NaH2PO2 solution A method for preparing single-phase Ru2P nanoparticles: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of 3×7 cm. 2 Then, 6200 μL of 0.05 M RuCl3 solution and 0.05 M NaH2PO2 mixed solution were added to the graphene substrate and vacuum dried for 12 h. The laser power was 2.7 W and the laser scribing rate was 5.5 × 10 5 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-supported Ru2P nanoparticles.
[0035] Embodiment 3: The solution composition and concentration are as follows: 0.05MRuCl3 solution and 0.1MNaH2PO2 solution A method for preparing single-phase Ru2P nanoparticles: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of 4×5 cm. 2Then, 8000 μL of 0.05 M RuCl3 solution and 0.1 M NaH2PO2 mixed solution were added to the graphene substrate and vacuum dried for 12 h. The laser power was 3 W and the laser scribing rate was 3.5 × 10 5 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-supported Ru2P nanoparticles.
[0036] Embodiment 4: The solution composition and concentration are as follows: 0.05M RuCl3 solution and 0.2M NaH2PO2 solution A method for preparing single-phase RuP nanoparticles: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of 4×4 cm. 2 Then, 900 μL of 0.05 M RuCl3 solution and 0.2 M NaH2PO2 mixed solution were added to the graphene substrate and vacuum dried for 12 h. The laser power was 1.5 W and the laser scribing rate was 3.5 × 10 5 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-supported RuP nanoparticles.
[0037] Embodiment 5: The solution composition and concentration are as follows: 0.05M RuCl3 solution and 0.2M NaH2PO2 solution A method for preparing single-phase RuP nanoparticles: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of 4×4 cm. 2 Then, 900 μL of 0.05 M RuCl3 solution and 0.2 M NaH2PO2 mixed solution were added to the graphene substrate and vacuum dried for 12 h. The laser power was 1.5 W and the laser scribing rate was 5.4 × 10 5 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-supported RuP nanoparticles.
[0038] Embodiment 6: The solution composition and concentration are as follows: 0.05M RuCl3 solution and 0.2M NaH2PO2 solution A method for preparing single-phase RuP nanoparticles: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of 9×9 cm. 2Then, 6900 μL of 0.05 M RuCl3 solution and 0.2 M NaH2PO2 mixed solution were added to the graphene substrate and vacuum dried for 12 h. The laser power was 1.5 W and the laser scribing rate was 6 × 10 5 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-supported RuP nanoparticles.
[0039] Embodiment 7: The solution composition and concentration are as follows: 0.05MRuCl3 solution and 2MNaH2PO2 solution A method for preparing single-phase RuP2 nanoparticles: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of 2×4 cm. 2 Then, 300 μL of 0.05 M RuCl3 solution and 2 M NaH2PO2 mixed solution were added to the graphene substrate and vacuum dried for 12 h. The laser power was 12 W and the laser scribing rate was 2.1 × 10 5 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-loaded RuP2 nanoparticles.
[0040] Embodiment 8: The solution composition and concentration are as follows: 0.05MRuCl3 solution and 2MNaH2PO2 solution A method for preparing single-phase RuP2 nanoparticles: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of 9×8cm. 2 Then, 9000 μL of 0.05 M RuCl3 solution and 2 M NaH2PO2 mixed solution were added to the graphene substrate and vacuum dried for 12 h. The laser power was 15 W and the laser scribing rate was 2.1 × 10 5 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-loaded RuP2 nanoparticles.
[0041] Embodiment 9: The solution composition and concentration are as follows: 0.05MRuCl3 solution and 2MNaH2PO2 solution A method for preparing single-phase RuP2 nanoparticles: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of 4×6 cm. 2Then, 7600 μL of 0.05 M RuCl3 solution and 2 M NaH2PO2 mixed solution were added to the graphene substrate and vacuum dried for 12 h. The laser power was 13 W and the laser scribing rate was 2.1 × 10 5 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-loaded RuP2 nanoparticles.
[0042] Embodiment 10: The solution composition and concentration are as follows: 0.05MRuCl3 solution and 2MNaH2PO2 solution A method for preparing single-phase RuP2 nanoparticles: First, a commercial polyimide film was laser scribed to obtain a graphene substrate with a scribed area of 10 × 10 cm 2 Then, 10000 μL of 0.05 M RuCl3 solution and 2 M NaH2PO2 mixed solution were added to the graphene substrate and vacuum dried for 12 h. The laser power was 17 W and the laser scribing rate was 2.1 × 10 5 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-loaded RuP2 nanoparticles.
[0043] Figure 1 The refined XRD spectra of Ru2P, RuP and RuP2 prepared by this method can be seen from the spectra. Except for the typical graphene peak (25.8°), the other peaks are all peaks of pure phase phosphide without other impurity phases. The refined spectrum 1 (A) corresponds to the standard Ru2P phase ICSD (43686), the refined spectrum 1 (B) corresponds to the standard RuP2 phase ICSD (42607), and the refined spectrum 1 (C) corresponds to the standard RuP phase ICSD (648015).
[0044] Figure 2 The simulated Raman results and experimental Raman spectra of Ru2P, RuP and RuP2 nanoparticles are shown in Figure 1. As can be seen from the spectra, the Raman peaks of the three ruthenium phosphides are consistent with the simulated standard Raman spectra.
[0045] Figure 3 The TEM morphology and high-resolution transmission electron microscopy images of Ru2P, RuP and RuP2 nanoparticles. Figure 3 In (A), 0.222nm and 0.236nm correspond to the (211) and (112) crystal planes of Ru2P, respectively. Figure 3 The 0.204 nm in (B) corresponds to the (211) crystal plane of RuP. Figure 3In (C), 0.386nm and 0.297nm correspond to the (201) and (020) crystal planes of RuP2, respectively.
[0046] Figure 4 The first cycle overpotential performance of Ru2P as the cathode material of lithium oxygen battery. Figure 4 It can be seen that the Li-O2 battery composed of Ru2P positive electrode material exhibits a lower overpotential (0.74V).
[0047] Figure 5 The cycling performance of Ru2P as the cathode material of lithium-oxygen battery at low current density (A) and high current density (B). Figure 5 As can be seen from (A), the Li-O2 battery composed of Ru2P positive electrode material shows excellent cycling performance, which is specifically manifested in low current density (100mAg -1 ) can stably cycle for 800h and high current density (500mAg -1 ) can circulate stably for 175h.
[0048] Embodiment 11: The laser preparation parameter range and reference critical value of Ru2P nanoparticles are as follows: The concentration of the ruthenium chloride aqueous solution used to prepare Ru2P nanoparticles is 0.05M; when the concentration of the sodium hypophosphite solution used is 0.05-0.1M, the molar ratio of the ruthenium chloride aqueous solution to the sodium hypophosphite solution in the mixed aqueous solution of the ruthenium chloride precursor salt and the sodium hypophosphite used is 1:(1-2). At this molar ratio concentration, nanoparticles of a mixed phase of Ru+Ru2P are generally prepared, which have problems such as phase impurity.
[0049] The concentration of the ruthenium trichloride aqueous solution used to prepare Ru2P nanoparticles is 0.05M; when the concentration of the sodium hypophosphite solution used is 0.05-0.1M, the molar ratio of the ruthenium trichloride aqueous solution to the sodium hypophosphite solution in the mixed aqueous solution of the ruthenium trichloride precursor salt and the sodium hypophosphite used is 1:(1-2). Single-phase Ru2P nanoparticles can be obtained by performing secondary scribing using the secondary scribing laser preparation parameters of single-phase Ru2P nanoparticles under the following conditions.
[0050] The secondary scribing laser preparation parameters of single-phase Ru2P nanoparticles are as follows: the secondary scribing laser power for preparing Ru2P nanoparticles is 2W-6W, more preferably 2W-4W; the secondary scribing laser rate for preparing Ru2P nanoparticles is 3.5×10 5 -7×10 5 mm / s.
[0051] The solution composition and concentration are as follows: 0.05MRuCl3 solution and 0.05-0.1MNaH2PO2 solution, for the concentration molar ratio of the two (C RuCl3 :C NaH2PO2 ) should be between (1:1-1:2). When the concentration ratio is less than 1:1, a Ru+Ru2P mixed phase will appear during laser scribing (Ru is the main component). When the concentration ratio is greater than 1:2, a Ru2P+RuP mixed phase will appear (Ru2P is the main component).
[0052] After the 0.05MRuCl3 solution and the 0.05-0.1MNaH2PO2 solution are determined, the laser power can be selected within (2W-4W). When it is greater than this laser power, there will be a trend of increasing the single phase of Ru. When it is less than this laser rate, no phase will appear.
[0053] When the 0.05M RuCl3 solution and the 0.05-0.1M NaH2PO2 solution are determined and the laser power is fixed within (2W-6W), the laser rate is within (3.5×10 5 -7×10 5 mm / s) can be used to prepare Ru2P. The maximum laser speed is 7×10 5 mm / s, when it is less than this laser speed, the Ru phase increases.
[0054] Proof and mechanism analysis: Figure 6 The XRD patterns of the compounds prepared under different laser parameters (laser power and laser rate) are shown. Figure 6 A shows that the laser rate is fixed at 1.4×10 5 mm / s, when the laser power is adjusted (4.5-9W), it appears as a single phase of Ru without any Ru2P phase. Figure 6 B shows the laser rate (7×10 4 mm / s-3.5×10 5 mm / s), the Ru phase decreases and the Ru2P phase increases with the increase of laser speed, until the laser speed exceeds 3.5×10 5 When the laser power is 0.1mm / s, it is pure phase Ru2P. The possible synthesis mechanism is: at higher laser power, due to the high temperature, RuCl3 is first reduced to Ru, and the high temperature accelerates the movement rate of PH3 gas decomposed from Na2H2PO2, causing a large amount of PH3 gas to be lost, so no phosphide is generated. After reducing the power, obvious Ru2P generation can be seen. When the power is constant, the faster laser rate determines the higher cooling rate. At a high cooling rate, Ru nanoparticles are smaller and have a larger surface energy, which will absorb more PH3 gas to form Ru2P phase.
[0055] Example 12: The laser preparation parameter range and reference critical value of RuP nanoparticles are as follows: The concentration of the ruthenium trichloride aqueous solution used to prepare RuP nanoparticles is 0.05M; when the concentration of the sodium hypophosphite solution used is 0.2M, the molar ratio of the ruthenium trichloride aqueous solution to the sodium hypophosphite solution in the mixed aqueous solution of the ruthenium trichloride precursor salt and the sodium hypophosphite used is 1:4. At this molar ratio concentration, nanoparticles of a mixed phase of Ru2P+RuP are generally prepared, which have problems such as phase impurity.
[0056] The concentration of the ruthenium trichloride aqueous solution used to prepare RuP nanoparticles is 0.05 M; when the concentration of the sodium hypophosphite solution used is 0.2 M, the molar ratio of the ruthenium trichloride aqueous solution to the sodium hypophosphite solution in the mixed aqueous solution of the ruthenium trichloride precursor salt and the sodium hypophosphite used is 1:4. Single-phase RuP nanoparticles can be obtained by secondary scribing using the laser preparation parameters for secondary scribing of single-phase RuP nanoparticles under the following conditions.
[0057] The secondary scribing laser preparation parameters of single-phase RuP nanoparticles are as follows: the secondary scribing laser power for preparing RuP nanoparticles is 1.5W-2.4W, more preferably 1.5W; the secondary scribing laser rate for preparing RuP nanoparticles is 2.1×10 5 -3.5×10 5 mm / s, more preferably 3.5×10 5 mm / s.
[0058] The solution composition and concentration are as follows: 0.05MRuCl3 solution and 0.2MNaH2PO2 solution, for the concentration molar ratio of the two (C RuCl3 :C NaH2PO2 ) should be (1:4). When the concentration ratio is less than 1:4, the situation in Example 11 will occur when laser scribing is used. When the concentration ratio is greater than 1:4, a RuP+RuP2 mixed phase will appear.
[0059] After the 0.05MRuCl3 solution and the 0.2MNaH2PO2 solution are determined, the laser power can be selected within (1.5W-2.4W). When the laser power is greater than this, there will be a trend of increasing the single phase of Ru2P (Figure 12A). When it is less than this laser rate range, no phase will appear.
[0060] When the 0.05M RuCl3 solution and the 0.2M NaH2PO2 solution are determined and the laser power is fixed within 1.5W, the laser rate is within 2.1×10 5 -3.5×105 mm / s), with the increase of laser speed, RuP increases continuously, and the laser speed is 3.5×10 5 When the laser speed is higher than 1000 nm, it is pure RuP phase. When the laser speed is higher than 1000 nm, it is still RuP phase. When the laser speed is lower than 1000 nm, the Ru2P phase increases.
[0061] Proof and mechanism analysis: Since the synthesis temperature of RuP is usually low, choosing a lower laser power is beneficial to the formation of RuP ( Figure 7 A). As the cooling rate continues to increase, the synthesis temperature is indirectly reduced, so we finally 5 Pure phase RuP was synthesized at a laser rate of mm / s.
[0062] Example 13: The laser preparation parameter range and reference critical value of RuP2 nanoparticles are as follows: The concentration of the ruthenium trichloride aqueous solution used to prepare RuP2 nanoparticles is 0.05M; when the concentration of the sodium hypophosphite solution used is 2M, the molar ratio of the ruthenium trichloride aqueous solution to the sodium hypophosphite solution in the mixed aqueous solution of the ruthenium trichloride precursor salt and the sodium hypophosphite used is 1:40. At this molar ratio concentration, nanoparticles of a mixed phase of RuP+RuP2 are generally prepared, which have problems such as phase impurity.
[0063] The concentration of the ruthenium trichloride aqueous solution used to prepare RuP2 nanoparticles is 0.05 M; when the concentration of the sodium hypophosphite solution used is 2 M, the molar ratio of the ruthenium trichloride aqueous solution to the sodium hypophosphite solution in the mixed aqueous solution of the ruthenium trichloride precursor salt and the sodium hypophosphite used is 1:40. Single-phase RuP2 nanoparticles can be obtained by secondary scribing using the laser preparation parameters for secondary scribing of single-phase RuP2 nanoparticles under the following conditions.
[0064] The laser preparation parameters for the secondary scribing of single-phase RuP2 nanoparticles are as follows: The laser rate for the secondary scribing of Ru2P nanoparticles is 2.1×10 5 mm / s. The secondary scribing laser power for preparing RuP2 nanoparticles is 9W-12W.
[0065] The solution composition and concentration are as follows: 0.05MRuCl3 solution and 2MNaH2PO2 solution, for the concentration molar ratio of the two (C RuCl3 :C NaH2PO2 ) should be 1:40. When the concentration ratio is less than 1:40, the situation in Example 11 or Example 12 will occur when laser scribing is used. When the concentration ratio is greater than 1:40, RuP2 single phase may appear.
[0066] When the 0.05 M RuCl3 solution and the 2 M NaH2PO2 solution were determined, the laser rate was 2.1 × 10 5 mm / s, the laser power can be selected within (9W-12W). When it is greater than this laser power, a single RuP2 phase will appear. When it is less than this laser power, a RuP phase will appear.
[0067] Proof and mechanism analysis: Figure 8 The XRD patterns of the compounds prepared under different laser parameters (laser power and laser rate) are shown. Figure 8 A shows the laser rate (1.4×10 4 mm / s–2.1×10 5 mm / s), it appears as a RuP+RuP2 mixed phase, but it can be found that the RuP2 phase gradually increases with the increase of laser rate. Figure 8 B shows the laser rate fixed at 2.1×10 4 mm / s, when the laser power is adjusted (4.5W-9W), the RuP phase decreases and the RuP2 phase increases with the increase of laser power. When the laser power reaches 9W, it shows a single RuP2 phase. The possible synthesis mechanism is: in the 2MNaH2PO2 precursor, at a higher laser power, it is more conducive to the decomposition of excess NaH2PO2, thereby promoting the synthesis of pure phase RuP2.
[0068] Furthermore, in summary, the above laser preparation can precisely control the phase structure of ruthenium phosphide. Under the same precursor and phosphorus source concentration, only the power and scratching rate need to be changed to prepare single-phase structured ruthenium phosphide nanoparticles. This preparation method has high universality and can be extended to the synthesis of phase-change iron phosphide and cobalt phosphide, and has good application prospects.
[0069] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing phase-change ruthenium phosphide nanoparticles by air laser scribing, characterized in that: The following steps are involved: A polyimide film is scratched with a laser to obtain a graphene substrate, and then a mixed aqueous solution of a ruthenium trichloride precursor salt and sodium hypophosphite is added dropwise to the graphene substrate. After vacuum drying, the graphene substrate is scratched again with a laser to obtain transition metal ruthenium phosphide of different phase compositions.
2. The method for preparing phase-change ruthenium phosphide nanoparticles by air laser scribing according to claim 1, characterized in that: When the polyimide film is scratched with a laser, the wavelength of the laser used is 10.6 μm.
3. The method for preparing phase-change ruthenium phosphide nanoparticles by air laser scribing according to claim 1, characterized in that: The laser scribing rate of the polyimide film is 7×10 3 mm / s-7×10 5 mm / s, laser power is 3W-9W, and the scratching area is (2-10)mm×(2-10)mm.
4. The method for preparing phase-change ruthenium phosphide nanoparticles by air laser scribing according to claim 1, characterized in that: The molar ratio of the ruthenium trichloride aqueous solution to the sodium hypophosphite solution in the mixed aqueous solution of the ruthenium trichloride precursor salt and the sodium hypophosphite is 1:(1-40).
5. The method for preparing phase-change ruthenium phosphide nanoparticles by air laser scribing according to claim 4, characterized in that: The concentration of the ruthenium trichloride aqueous solution is 0.05M.
6. The method for preparing phase-change ruthenium phosphide nanoparticles by air laser scribing according to claim 4, characterized in that: The concentration of the sodium hypophosphite solution is 0.05M-2M.
7. The method for preparing phase-change ruthenium phosphide nanoparticles by air laser scribing according to claim 1, characterized in that: The amount of the mixed aqueous solution of the ruthenium trichloride precursor salt and sodium hypophosphite added is (80-10000) μL.
8. The method for preparing phase-change ruthenium phosphide nanoparticles by air laser scribing according to claim 1, characterized in that: The laser scribing rate of the secondary scribing is controlled to be 7×10 3 mm / s-7×10 5 mm / s, the laser power is 1W-20W, and the scratching area is the same as the graphene substrate area.
9. A phase-change ruthenium phosphide nanoparticle prepared by the air laser scratching preparation method of phase-change ruthenium phosphide nanoparticles according to any one of claims 1 to 8, characterized in that: The phase-change ruthenium phosphide nanoparticles are Ru2P, RuP and RuP2.
10. Use of the phase-change ruthenium phosphide nanoparticles according to claim 9 as positive electrode material in button-type Li-O2 batteries.